2018
DOI: 10.1002/adsu.201800031
|View full text |Cite
|
Sign up to set email alerts
|

Solar Redox Flow Batteries: Mechanism, Design, and Measurement

Abstract: The increasing public awareness of the energy crisis since the 1970s has promoted the ongoing development of energy conversion and storage systems. As a supplement to photovoltaics, photoelectrochemical cells (PECs) are among the promising solar electricity generation systems. However, the intrinsic intermittence of sunlight can never guarantee continuous electricity supply. Therefore, PECs are being developed to convert solar energy to chemical energy in the forms of fuels such as H2 and other organic chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 257 publications
0
23
0
Order By: Relevance
“…To address the above issues, an appealing solution is integrating photoelectric conversion parts into rechargeable batteries with the simplest two‐electrode configuration for the direct conversion and/or storage of the solar energy in one single device . Until more recently, the increasing interests have been concentrated on the straight internal combination of photoelectrodes with various types of batteries such as Li‐ion batteries and Li‐air batteries etc . In these developed photo‐responsive two‐electrode systems, the solar energy not only can be directly stored during charging process to achieve various photoassisted/photocharging rechargeable batteries, but also promote discharging performance via photoelectric effects in some devices.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above issues, an appealing solution is integrating photoelectric conversion parts into rechargeable batteries with the simplest two‐electrode configuration for the direct conversion and/or storage of the solar energy in one single device . Until more recently, the increasing interests have been concentrated on the straight internal combination of photoelectrodes with various types of batteries such as Li‐ion batteries and Li‐air batteries etc . In these developed photo‐responsive two‐electrode systems, the solar energy not only can be directly stored during charging process to achieve various photoassisted/photocharging rechargeable batteries, but also promote discharging performance via photoelectric effects in some devices.…”
Section: Introductionmentioning
confidence: 99%
“…In another design shown in Figure 15b, the two electrochemical cells can be integrated. Since in both configurations, the storage in an SFB requires external tanks, SFBs are suitable for power plants, not small electronics [72] . Hence, the details of different approaches are not discussed here, and we encourage enthusiastic readers to follow the related publications.…”
Section: Review Of Hybrid Cellsmentioning
confidence: 99%
“…2 Simultaneous solar energy conversion and storage have received increasing interest for efficiently utilizing the abundant yet intermittent solar energy. 3 Solar rechargeable batteries combine the advantages of photoelectrochemical (PEC) devices and batteries and have emerged as an attractive alternative to artificial photosynthesis for large-scale solar energy harvesting and storage. 3 Under the irradiation of sunlight, the photo-generated electron-hole pair can drive the redox reactions, which makes the integration of a solar cell and RFB possible.…”
Section: And T Leo Liu 1 *mentioning
confidence: 99%
“…3 Solar rechargeable batteries combine the advantages of photoelectrochemical (PEC) devices and batteries and have emerged as an attractive alternative to artificial photosynthesis for large-scale solar energy harvesting and storage. 3 Under the irradiation of sunlight, the photo-generated electron-hole pair can drive the redox reactions, which makes the integration of a solar cell and RFB possible. In fact, recent studies have demonstrated the feasibility of integrating semiconductor solar cells and RFBs.…”
Section: And T Leo Liu 1 *mentioning
confidence: 99%